Obstetric and gynaecological ultrasound : How, why and when - Chudleigh, Trish (Elsevier, 2017)
Obstetric and Gynaecological Ultrasound is a highly illustrated manual ideal that covers the full range of obstetric and gynaecological ultrasound examinations undertaken within a secondary referral setting. It combines the practicalities of how to perform these examinations with the information needed to interpret the findings and construct a clinically useful report. Explains the principles of grey scale ultrasound, Doppler ultrasound and instrumentation; Addresses problems from both practical and clinical viewpoints; Provides comparative images showing results of good and bad scanning techniques;...